Blood oath - Urszenyi, Steve (An Alex Martel thriller, 2025)
"In this action-packed thriller, Special Agent Alex Martel's fight becomes personal when her father is abducted by rebel forces. In the heart of Africa, CIA Special Agent Alexandra Martel's safari with her father spirals into a deadly game of betrayal when he is kidnapped by rebels. Suddenly, her peaceful Serengeti vacation transforms into a desperate race against time. As the general is held by local rebels, Russian mercenaries and Chinese MSS operatives descend on East Africa, all hunting the military secrets locked in her father's mind. Alex assembles an elite team to navigate the treacherous terrain, but complications arise when her CIA boss, Caleb, shows up unexpectedly, stirring feelings she's tried to bury since her husband's death. As competing forces close in, Alex uncovers betrayals stretching from the Serengeti to the highest levels of global intelligence. Trust becomes as scarce as water in the African savanna. With enemies converging from all sides, Alex must embrace her darkest instincts to save her father. But in a world where allies become enemies, and nothing is as it seems, how much of herself is she willing to sacrifice to honor the bonds of blood?"-- Provided by publisher.